Peran Guru Agama Hindu dalam Internalisasi Ajaran Catur Paramita untuk Menumbuhkan Karakter Cinta Kasih Siswa di SDN 9 Sumerta - Arinata, I Nyoman Budi (Samsara Institute Publisher, 2025)
This study aims to describe the role of Hindu religious education teachers in internalizing the teachings of Catur Paramita to foster the character of loving-kindness among students at SDN 9 Sumerta. The Catur Paramita teachings maitri (loving kindness), karuna (compassion), mudita (sympathetic joy), and upeksha (equanimity) serve as a fundamental foundation in shaping students’ characters to be caring and empathetic toward others. The research employs a qualitative descriptive approach, utilizing observation, in-depth interviews, and documentation as data collection techniques. The findings indicate that Hindu religion teachers play a strategic role as role models, facilitators, and motivators in instilling Catur Paramita values through thematic lessons, integration of values in daily activities, and reinforcement via direct practices such as social service, group prayers, and value-based discussions. The internalization of Catur Paramita has proven effective in nurturing students' loving character, as reflected in their attitudes of respect, helpfulness, empathy, and tolerance in school social interactions. The study recommends enhancing teacher training in value-based Hindu spiritual pedagogy as part of a holistic character education approach.